USER ACCEPTANCE OF DATA INFORMED DECISION MAKING PORTALS: APPLICATION OF THE UTAUT MODEL AND LEADERSHIP STYLES - Jefri Marzal; Rizqa Raaiqa Bintana; Pradita Eko Prasetyo Utomo (Journal of Business Studies and Management Review, 2021)
In general, to make decisions in the discipline of information systems are divided into two, namely Decision Support System (DSS) and Data Informed Decision Making (DIDM). DIDM is a data-driven decision-making process taking into account previous experience, user research, and other important information. Many applications are categorized as data-informed for universities, one of which is a portal that contains data or information about various aspects of a university. There are not many known factors that influence leaders to use informed data as a tool for making decisions. This study applies the UTAUT (Unified Theory of Acceptance and Use of Technology) model by adding a leadership style variable as a moderating variable. Hypothesis testing using the bootstrapping technique in this study involved a number of samples (N) of 300, testing for the two-tailed hypothesis, using a significance level of 5%. Based on the test results revealed only facilitating conditions that affect use behavior. Meanwhile, the variables of performance expectancy, effort expectancy, and social influence have no effect on behavioral intention to use the application. In addition, it was also found that the moderator variable of leadership style did not affect the relationship between performance expectancy, effort expectancy, social influence, and facilitating conditions with the intention and actual use of leaders in data informed applications to make decisions.